2004
DOI: 10.1002/prep.200400058
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameters of Nitramines Influencing Shock Sensitivity

Abstract: TNO Prins Maurits Laboratory has actively followed and contributed to the research on the development of insensitive munitions (IM). One of the initial research topics at TNO focused on the improvement of the shape of RDX crystals and its relation to the shock sensitivity. The variation of crystal shape has been studied by crystallization from different solvents and/or by post‐treatment of the crystals. The role of the mean particle size on shock sensitivity was also included in these analyses. The decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…It was proposed that this decrease in impact sensitivity comes from a reduction of imperfections or dislocations in a crystal. Also, it has been shown that particles with a spherical shape are less sensitive to initiation as well [74,75].…”
Section: Ii14 Ultra-high Pressure Supercritical Fluid Processing Ofmentioning
confidence: 99%
“…It was proposed that this decrease in impact sensitivity comes from a reduction of imperfections or dislocations in a crystal. Also, it has been shown that particles with a spherical shape are less sensitive to initiation as well [74,75].…”
Section: Ii14 Ultra-high Pressure Supercritical Fluid Processing Ofmentioning
confidence: 99%
“…The collapse of voids of sub‐micron dimensions is crucial for the initiation and stable propagation of a detonation. We are able to control the shock sensitivity of explosives, albeit empirically, by controlling the defect content of the explosive grains and through processing steps that reduce the severity of stress concentrators .…”
Section: Introductionmentioning
confidence: 99%
“…The effort was motivated by the progress on studying and controlling of voids (e.g. empty space) in explosives for insensitive munitions [3][4][5][6][7][8][9][10][11][12][13], as voids can assist the formation of hot spots, igniting the surrounding materials and leading to detonation under external mechanical stimuli such as shocks or impacts [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%